2002
DOI: 10.1111/j.1541-0072.2002.tb02160.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multiple Streams Model of U.S. Foreign Aid Policy

Abstract: This study builds an interactive, quantitative model to explain U.S. foreign aid allocations. We develop an explanation based on Kingdon's multiple streams model to argue that aid decisions are the result of trade ties, socialist orientation, human needs, and the political ideologies of the administration and the senate interacting with adjustments to baseline funding. We find that there are significant conditional relationships between economic and security‐related assistance and our external and domestic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 25 publications
1
75
0
1
Order By: Relevance
“…Indeed, MSM has been used to guide policy research across a wide range of policy domains and institutional settings (eg., Kingdon, 1995;Oliver, 1991;Shibuya, 1997;Travis & Zahariadis, 2002;Zahariadis, 1992Zahariadis, , 1995Zahariadis, , 1996 and has shown promise in explaining educational agenda setting in the U.S. and other countries. (DeJaeghere, Chapman, Mulkeen, 2006;Edlefson, 1993;Holderness, 1992;Houlihan & Green, 2006;Lieberman, 2002;Stout & Stevens, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Indeed, MSM has been used to guide policy research across a wide range of policy domains and institutional settings (eg., Kingdon, 1995;Oliver, 1991;Shibuya, 1997;Travis & Zahariadis, 2002;Zahariadis, 1992Zahariadis, , 1995Zahariadis, , 1996 and has shown promise in explaining educational agenda setting in the U.S. and other countries. (DeJaeghere, Chapman, Mulkeen, 2006;Edlefson, 1993;Holderness, 1992;Houlihan & Green, 2006;Lieberman, 2002;Stout & Stevens, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They used a quantitative model to explain the U.S. foreign aid allocations based on Kingdon's model. Interestingly, Travis and Zahariadis () made note of the lack of quantitative work being produced using multi‐streams model and our research found that the scenario has not changed since. Our search found only one another journal study (by Robinson and Eller ), which argued that Kingdon's model does provide falsifiable predictions, and that employed a quantitative model to test these predictions.…”
Section: Resultsmentioning
confidence: 72%
“…There are very few studies that apply or utilize Kingdon's multistream model using quantitative methods and sampling techniques. One study, that for the first time defied the qualitative nature of studies based on Kingdon's model, was by Travis and Zahariadis (). They used a quantitative model to explain the U.S. foreign aid allocations based on Kingdon's model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps it is the case that when Democrats control Congress, it is other types of aid, specifically economic support funds (ESF), which are used to promote economic and political stability through balance‐of‐payments support, that are most likely to bear the brunt of cuts for those countries with poor democratic practices. Indeed, Travis and Zahariadis (2002) find that Senate Democrats have a proclivity to raid ESF funding while continuing their support for economic assistance. Additionally, one can argue that economic aid given to abusive regimes is the type most likely to still benefit poor citizens while ESF aid would only prop up an abusive government.…”
Section: Resultsmentioning
confidence: 99%